Mother-child pairs’ eating and feeding behaviours in two different nutritional status from two distinct provinces - Gülsüm Özen; Bülent Güneş; Suzan Yalçın; Sıddika Songül Yalçın (BMC Pediatrics, 2024)
Abstract Nutrition plays a crucial role for the bio-psycho-social growth and development of children. Mother-child pairs’ eating-feeding problems can be hypothesized to relate to the child’s nutritional status and living area. Our focus was to assess maternal attitudes and children’s eating habits in thin and normal-weight children across two cities characterized by distinct socioeconomic and demographic profiles: Ankara and Şanlıurfa. This double case-control study included the mothers whose children are aged between 2 and 7 years old in both cities. Figure Rating Scale, Child Feeding Questionnaire and Behavioral Pediatrics Feeding Assessment Scale were filled by mothers of children. The mothers of thin children were concerned more about the weight of their children, felt more responsible for feeding their children, and use of pressured them to eat more frequently compared to normal-weight children’s mothers in both cities. In Ankara, the duration of breastfeeding is longer, using formula is rarer and starting complementary food on time is more common, mother had higher scores on perceived responsibility, perceived child weight, and concern about child weight subscales; lower score on the restriction subscale compared to Şanlıurfa. Mothers of both thin and normal weight children in Şanlıurfa rated their children as weaker compared to those in Ankara. In conclusion, child eating behaviors and parental feeding practices were associated with the weight of children depending on demographic and sociocultural differences. Implementing customized, location-specific preventive educational initiatives on child feeding will not only foster behavioral changes but also yield valuable insights for shaping future interventions.